1999
DOI: 10.1002/1531-8249(199908)46:2<260::aid-ana18>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue copper and manganese content in the lentiform nucleus in primary adult-onset dystonia

Abstract: We analyzed trace metals in frozen brain tissue of several subcortical nuclei from 3 patients with primary adult‐onset dystonia and 10 control subjects. Copper levels were significantly increased in the globus pallidus and putamen of patients with dystonia. A slight increase in manganese content was identified in the putamen and thalamus of patients with dystonia. Our findings show for the first time an accumulation of trace metals in the lentiform nuclei in patients with primary dystonia, which may play a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…Similar sonographic findings have been obtained in a high proportion of patients with a focal or generalized primary adult‐onset dystonia 3, 4. Recent studies on brain tissue of patients with primary dystonia have demonstrated that the increased brightness (echogenicity) of the lentiform nuclei on TCS might be related by an elevated tissue copper content 5. It is well known that an increase in synaptic copper concentration may modulate receptor activity6–10 and consequently the neuronal output of the basal ganglia loop 11.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Similar sonographic findings have been obtained in a high proportion of patients with a focal or generalized primary adult‐onset dystonia 3, 4. Recent studies on brain tissue of patients with primary dystonia have demonstrated that the increased brightness (echogenicity) of the lentiform nuclei on TCS might be related by an elevated tissue copper content 5. It is well known that an increase in synaptic copper concentration may modulate receptor activity6–10 and consequently the neuronal output of the basal ganglia loop 11.…”
supporting
confidence: 65%
“…In patients with primary dystonia we were able to demonstrate an increased copper concentration in the lentiform nuclei. This may explain the elevated echogenicity as well as shift of T2 values and may play a role in the pathogenesis of dystonic movements disorders 5, 12. Copper may influence receptor function and basal ganglia neuronal activity that may result in a disinhibition of the motor cortex and dystonic movements and postures 6–10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Neuropathological examinations in patients with idiopathic dystonia revealed sig nifi cantly increased copper levels in the globus pallidum and putamen compared with control brain samples. 37 Further neuropathological and multimodal imaging studies are needed to elucidate the pathogenesis of the hyper echogenicities in patients with Huntington disease. Regarding brain atrophy, the sonographic evaluation of the ventricular system, including ventricular enlargement, has been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…As hyperechogenicity in the parenchymal sonography was believed to be due to metal accumulation, a post mortem analysis was performed in individuals suffering from dystonia. This study could rule out an increased copper and manganese content in the lenticular nucleus compared to controls [16]. Recently, our group was able to show, that patients suffering from neurodegeneration with brain iron accumulation (NBIA), a disease with childhood onset which is caused by mutations in enzymes dealing with iron metabolism in the brain, also shows increased echogenicity in the SN compared to healthy controls [17].…”
Section: Other Movement Disordersmentioning
confidence: 99%